THE PERSONALITY ASPECTS OF THE MAIN CHARACTERS IN NOVEL MENCARI NAMA TUHAN YANG KESERATUS WORKS BY AMIN MAALOUF - Risky Ayu Lestari; La Ode Syukur; La Ode Balawa (CASA CENDEKIA MEDIA, 2025)
This study aims to describe the personality of the main character in Amin Maalouf's novel The 100th Name of God. This study uses the library research method and is a descriptive qualitative study. The data used in this study is written data in the form of words and sentences related to the personality aspects of the main character in Amin Maalouf's novel The 100th Name of God, published in 2021. This study shows that the personality aspects possessed by the main character based on Jung's theory are 1) consciousness (unconsciousness), 2) personal unconscious, 3) collective unconscious, and 4) personality type, which is a combination of attitudes and functions that operate in the conscious and unconscious, namely introversion-sensing and introversion-feeling. This study concludes that there are five (5) personality aspects possessed by the main character in Amin Maalouf's novel The Hundredth Name. The five (5) personality aspects are 1) consciousness (consciousness), 2) personal unconsciousness (personal unconscious), 3) collective unconsciousness (collective unconscious) operating in the shadow, and 4) personality types operating in sensation-intuition and feeling-intuition.